PENGARUH CENDAWAN MIKORIZA ARBUSKULA TERHADAP PERTUMBUHAN BIBIT PANILI (Vanilla planifolia Andrews) - Octivia Trisilawati; Cecep Firman (Pusat Penelitian dan Pengembangan Perkebunan, 2004)
The effect of micorrhiza abuscular on the growth of vanilla cuttings (Vanilla flanifoliaAndrews)Mycorrhiza inoculation at nursery represent an effort to gain better quality and growth of vanilla,s cutting. A research aiming at the effect of arbuscular mycorrhiza (AM) inoculation on the growth of vanilla,s cutting was conducted in the green house of the Sukamulya ExperimentalGarden-Sukabumi, Indonesian Spices and Medicinal Crops Research Institute, from April 2002 to August 2002. A complete randomized design was used, arranged factorially with 2 factors and 3 replications. The first factor was vanilla types, consisted of Gisting and Anggerek, and the second factor was AM inoculation, such as without AM, 500 spores ofAM-p/plant, and 500 spores of Mycofer/plant. AM-p was a mixture of Acaulospora spp. and Glomus sp., while Mycofer was a mixture of Glomus sp., Glomus etunicatum, Gigaspora margarita, and Acaulospora sp. The result indicated that there was no significant interaction between vanilla type and AM inoculation on the plant growth. AM inoculation significantly affected the plant height, number of leaves, stem diameter, leaf area index, and dry weight of biomass. The difference of vanilla type significantly affected the root dry weight and precentage of AM root infection, but the interaction 19between AM and vanilla type did not significantly affect the plant growth. AM-pinoculation increased the plant height, number of leaves, stem diameter, leaf area index, and dry weight of biomass equal to 31,62%, 16,94%, 6%, 25,45% and 47,05%, while Mycofer increased those parameter 49,64%, 32,01%, 6%, 32,41% and 54,85%, respectively. The Anggerek type showed better responses to the AM inoculation than the Gisting type.